Strategi Literasi Digital Marketing pada Usaha Mikro Kecil dan Menengah (UMKM) oleh Pusat Layanan Usaha Terpadu (PLUT) Kabupaten Jember - Hidayatullah, M.F; Susanti, Vera; Salsabila, Raudhia Nur Salsabila (Mabny: Journal of Sharia Management and Business, 2023)
PLUT KUMKM Jember Regency is a program of the Ministry of Cooperatives and SMEs (KemenkopUKM) to encourage SMEs to advance to class. One of the tasks of PLUT KUMKM Jember Regency is to provide assistance to friends of MSMEs assisted by PLUT Jember Regency. One of the assistance is regarding digital marketing. In this assistance, PLUT holds independent classes and also Bimtek (Technical Guidance) classes for the assisted MSMEs. Through a series of digital marketing training and assistance applied to MSMEs in Jember Regency, they not only go through a learning process, but also become technologically literate, realizing that in this technological era, digital marketing is an inevitable necessity. This provides a new perspective on the incredible potential that digital marketing strategies have. MSMEs realize that digital marketing has the ability to reach target customers efficiently and effectively. This allows MSMEs to find consumers more quickly, precisely and widely, opening up huge opportunities for sustainable business growth. By implementing the right digital marketing strategy, it is estimated that MSME sales have the potential to increase by up to 70%, creating an extraordinary positive impact on local economic progress and the business desires of MSMEs themselves.